Defect-free SnTe topological crystalline insulator nanowires grown by molecular beam epitaxy on graphene. Issue 44 (7th November 2018) - Sadowski, Janusz; Dziawa, Piotr; Kaleta, Anna; Kurowska, Bogusława; Reszka, Anna; Story, Tomasz; Kret, Sławomir
Abstract : SnTe topological crystalline insulator nanowires have been grown by molecular beam epitaxy on graphene/SiC substrates. Abstract : SnTe topological crystalline insulator nanowires have been grown by molecular beam epitaxy on graphene/SiC substrates. The nanowires have a cubic rock-salt structure, they grow along the [001] crystallographic direction and have four sidewalls consisting of {100} crystal planes known to host metallic surface states with a Dirac dispersion. Thorough high resolution transmission electron microscopy investigations show that the nanowires grow on graphene in the van der Waals epitaxy mode induced when the catalyzing Au nanoparticles mix with Sn delivered from a SnTe flux, providing a liquid Au–Sn alloy. The nanowires are totally free from structural defects, but their {001} sidewalls are prone to oxidation, which points out the necessity of depositing a protective capping layer in view of exploiting the magneto-electric transport phenomena involving charge carriers occupying topologically protected states.